Culture, technology, communication : common world, different futures : 10th IFIP WG 13.8 International Conference, CaTaC 2016, London, June 15-17 2016, revised selected papers /: common world, different futures : 10th IFIP WG 13.8 International Conference, CaTaC 2016, London, June 15-17 2016, revised selected papers. (2016) - Unknown
No abstract available